2017
DOI: 10.1159/000452357
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Presence of Lymphovascular Invasion in Small Rectal Neuroendocrine Tumors on Immunohistochemical Analysis

Abstract: Rectal neuroendocrine tumors (RNETs) have become common in recent years and are good candidates for endoscopic resection (ER). To achieve clear resection margins, more advanced techniques such as endoscopic submucosal dissection, endoscopic submucosal resection with a ligation device, and cap-assisted endoscopic mucosal resection are available for ER. After ER, lymphovascular invasion (LVI) is regarded as an important predictor of nodal metastasis. Previous studies have shown that small RNETs with LVI were unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although additional surgery should be considered in patients with rectal NETs harboring lymphovascular invasion, this approach needs further validation because the reported prevalence of lymphovascular invasion ranges widely from approximately 1% to a little less than 60% [14,26]. Recently, immunohistochemical staining has been increasingly used for the accurate diagnosis of lymphovascular invasion [26][27][28]. Sekiguchi et al [28] retrospectively revealed that immunohistochemical staining identified almost half of the rectal NETs with lymphovascular invasion, while routine H-E staining identified only 1.2% in the same sample.…”
Section: Discussionmentioning
confidence: 99%
“…Although additional surgery should be considered in patients with rectal NETs harboring lymphovascular invasion, this approach needs further validation because the reported prevalence of lymphovascular invasion ranges widely from approximately 1% to a little less than 60% [14,26]. Recently, immunohistochemical staining has been increasingly used for the accurate diagnosis of lymphovascular invasion [26][27][28]. Sekiguchi et al [28] retrospectively revealed that immunohistochemical staining identified almost half of the rectal NETs with lymphovascular invasion, while routine H-E staining identified only 1.2% in the same sample.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine tumors (NETs), which arise from neuroendocrine cells, are rare, and rectal NETs account for about one-third of all gastrointestinal NETs [1][2][3]. The incidence of rectal NETs is increasing with the development of better diagnostic tools and improved knowledge [4].…”
Section: Introductionmentioning
confidence: 99%